Good environmental practices in households of Metropolitan Valparaíso, Chile - Castañeda-Meneses, Patricia Lorena (2024)
In Chile, the main issues affecting the quality of life of the population include air pollution, scarcity and contamination of water resources, degradation, loss, and pollution of soils, nuisance noise, solid waste management, and loss of biodiversity. In response to this situation, good environmental practices emerge in households, which can be characterized as simple and useful measures that individuals can adopt in their daily lives to reduce the negative environmental impact of their activities. In this context, the article presents the results of a qualitative research aimed at identifying and classifying the environmental practices carried out in households in Metropolitan Valparaíso, Chile. Methodologically, an exploratory-descriptive approach study was conducted, gathering information from 64 households through semi-structured interviews. The results show the implementation of good environmental practices in the household, related to the recycling of organic and non-organic waste, reusing organic and non-organic waste, and reducing the consumption of natural resources. It is concluded that the environmental practices developed by individuals in their households are motivated by a deep concern for environmental issues and seek to reduce the long-term negative consequences that will affect the living conditions of future generations. From an integrated perspective, the good environmental practices carried out in the household represent a silent and persevering microsocial dynamic that challenges the devastating actions of global economic, political, and technological actors regarding the use of natural resources.